Shear strengthening of full-scale RC beams with externally bonded ultra-high performance concrete (UHPC) plates with embedded CFRP strips - Guolin Wang; Lei Gu; Jingjiao Nie; Tao Qu; Chang Wu; Yuxuan Zhang; Jialin Yang (Case Studies in Construction Materials)
This study investigates experimentally the shear behavior of reinforced concrete (RC) beams strengthened with ultra-high performance concrete (UHPC) plates and carbon fiber-reinforced polymer (CFRP) strips. Six full-scale RC beams, including one control specimen and five strengthened with UHPC plates (with/without embedded CFRP strips), were tested to evaluate the contributions of UHPC plates and CFRP strips. Experimental results demonstrated that all beams failed in shear. Compared to the control beam, the strengthened beams exhibited significant improvements in shear capacity (with a 16.5–31.9 % increase), stiffness, and ductility. The embedded CFRP strips further enhanced cracking resistance of UHPC plates. Experimental findings also revealed that the composite action between UHPC plates and RC beams relies on the bond strength of the adhesive layer and the anchorage constraint of bolts. During the early stages of loading, the structural adhesive plays a dominant role, while in later stages, the bolts dominate, not only providing lateral restraint but also acting as shear connectors to mitigate possible slippage between the beam and the UHPC plate. These findings provide practical guidance for shear strengthening of RC beams with UHPC plates.